The Presence of (1→3)-β-D-Glucan as Prognostic Marker in Patients After Major Abdominal Surgery. (10th September 2020) - White, P Lewis; Posso, Raquel; Parr, Christian; Price, Jessica S; Finkelman, Malcolm; Barnes, Rosemary A
Abstract: Background: While the serological detection of (1→3)-β-D-glucan (BDG) can indicate invasive fungal disease (IFD), false positivity occurs. Nevertheless, the presence of BDG can still be recognized by the host's innate immune system and persistent BDG antigenemia, in the absence of IFD, can result in deleterious proinflammatory immune responses. Methods: During the XXX (INTENSE) study into the preemptive use of micafungin to prevent invasive candidiasis (IC) after abdominal surgery, the serum burden of BDG was determined to aid diagnosis of IC. Data from the INTENSE study were analyzed to determine whether BDG was associated with organ failure and patient mortality, while accounting for the influences of IC and antifungal therapy. Results: A BDG concentration >100 pg/mL was associated with a significantly increased Sequential Organ Failure Assessment score (≤100 pg/mL: 2 vs >100 pg/mL: 5; P < .0001) and increased rates of mortality (≤100 pg/mL: 13.7% vs >100 pg/mL: 39.0%; P = .0002). Multiple (≥2) positive results >100 pg/mL or a BDG concentration increasing >100 pg/mL increased mortality (48.1%). The mortality rate in patients with IC and a BDG concentration >100 pg/mL and ≤100 pg/mL was 42.3% and 25.0%, respectively. The mortality rate in patients without IC but a BDG concentration >100 pg/mL was 37.3%. The use of micafungin did not affect the findings. Conclusions: The presence of persistent or increasing BDG in the patient's circulation is associated with significant morbidity and mortality after abdominal surgery, irrespective of IC. The potential lack of a specific therapeutic focus has consequences when trying to manage these patients, and when designing clinical trials involving patients where host-associated BDG concentrations may be elevated. Clinical Trials Registration: NCT01122368. Abstract : Persistent (1→3)-β-D-glucan antigenemia, in the absence of invasive fungal disease, can result in proinflammatory immune responses in the host leading to increased morbidity and mortality that is clinically difficult to manage.